The Universe as Image: The Poetics of Marosa di Giorgio (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This paper focuses on the poetics of the Uruguayan writer, Marosa di Giorgio Médecis. Its purpose is to elucidate Di Giorgio's concept of image as an expressionistic revelation of the universe, and her idea of imagination as an integrating force of nature. Di Giorgio's writing captures the erotic and mystic dimensions of nature in a unified manner. Such an approach is also peculiar to her own écriture. In order to support my postulate. I analyze her prose, her poetry, her own idea on art, included in her literary manifesto "Wild Carnations" and Percy Shelley's reflections on romanticism.
Keywords: Marosa di Giorgio; Uruguayan poetry; image in poetry; romanticism